Nilai Perusahaan dan Faktor-Faktor Yang Mempengaruhinya pada Sektor Industri Barang Konsumsi yang Terdaftar Di BEI Periode 2015 – 2018 - Ririn Nafisa Ulfa; Hidayat Wiweko (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
The current development of the Indonesian economy can be said to be getting better as evidenced by the existence of development in all fields, including development in the economic field. The increasing development in the economic sector is marked by the increasing growth of the manufacturing industry in Indonesia as the largest contributor to the Indonesian economy, which of course attracts investors to invest. Before an investor will decide whether to invest their funds in a company, there is the most important activity that needs to be carried out, namely a careful assessment of the company. This study aims to determine the effect of working capital turnover, board diversity, and intellectual capital on firm value. The sample in this study was taken using purposive sampling method and obtained as many as 31 sample companies. The results showed that the variable of working capital turnover and the presence of a female board of directors had no effect on firm value, while the variables of educational background, work experience, and intellectual capital had a positive effect on firm value.